2014
DOI: 10.1016/j.toxicon.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

A lectin from Bothrops leucurus snake venom raises cytosolic calcium levels and promotes B16-F10 melanoma necrotic cell death via mitochondrial permeability transition

Abstract: BlL, a galactose-binding C-type lectin purified from Bothrops leucurus snake venom, exhibits anticancer activity. The current study was designed to elucidate the cellular mechanisms by which BlL induces melanoma cell death. The viabilities of B16-F10 melanoma cells and HaCaT keratinocytes treated with BlL were evaluated. Necrotic and apoptotic cell death, cytosolic Ca(2+) levels, mitochondrial Ca(2+) transport and superoxide levels were assessed in B16-F10 melanoma cells exposed to BlL. We found that treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…The result of this assay showed the reduction of MTT to absolute values of 0.03 and 0.07 of BJ and BE, respectively, thus confirming the cytotoxicity of these venoms in SiHa and HeLa cell lines. According to Aranda-Souza et al [30], a reduction was also observed of melanoma cells (B16-F10) when treated with a lectin extracted BIL in B. leucurus snake venom. When Nunes et al [31] used BIL venom of the same species B. leucurus in K562 cells (erythromyeloblastoid human leukemia cell line), it showed the cytotoxic activity, while HaCaT cells (normal cell) were not affected.…”
Section: Discussionmentioning
confidence: 91%
“…The result of this assay showed the reduction of MTT to absolute values of 0.03 and 0.07 of BJ and BE, respectively, thus confirming the cytotoxicity of these venoms in SiHa and HeLa cell lines. According to Aranda-Souza et al [30], a reduction was also observed of melanoma cells (B16-F10) when treated with a lectin extracted BIL in B. leucurus snake venom. When Nunes et al [31] used BIL venom of the same species B. leucurus in K562 cells (erythromyeloblastoid human leukemia cell line), it showed the cytotoxic activity, while HaCaT cells (normal cell) were not affected.…”
Section: Discussionmentioning
confidence: 91%
“…Plant seed lectin changes mitochondrial membranes leading to increased cytoplasmic calcium concentration and consequent reactive oxygen production, which induces necrotic cell death (Irigoin et al, 2009; Fernandes et al, 2010; Aranda-Souza et al, 2014). Even crude extract, the most unpurified fraction of latex, did not cause cytotoxicity in both cells, indicating that other components present did not damage these cells.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis will be tested in the future by checking HIF-1α expression in the control and treated group. Accumulated evidence shows that several isolated or recombinant snake venom toxins exhibit anti-cancer effects in vitro and in vivo preclinical models, triggering cell death via the mitochondrial intrinsic apoptotic pathway or necrosis [1,11,32]. Our results revealed that obtustatin did not induce any signs of apoptotic death in the treatment of animals with sarcoma.…”
Section: Discussionmentioning
confidence: 53%